GAMBARAN SANITASI TEMPAT PENGELOLAAN PANGAN DI WILAYAH PERMETER PELABUHAN TANJUNGWANGI BANYUWANGI 2022 - Aisyaroh, Septia Hilda; Lestari, Kusuma Scorpia; Yudhastuti, Ririh (Dian Nuswantoro Semarang, 2023)
Food Management Place (TPP) is a place used as production for ready-to-eat processed food starting from preparation, processing, packaging, storage, presentation to transportation which is carried out under supervision, including in the port area. The port is a meeting place for many people from various regions because the port is the entrance to an area, so it can potentially spread diseases that can cause health emergencies. The purpose of this study is to find out the description of TPP sanitation in the Tanjungwangi Port perimeter area, Banyuwangi. The research method used is through observation and interviews. Sampling used the total population in the Tanjungwangi Port perimeter area, which was as many as 6 TPPs were observed. The variable assessment uses a score calculation of all variables with a minimum value of 80 in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 14 of 2021 concerning Standards for Business Activities and Products in the Implementation of Health Sector Risk-Based Business Licensing. The results of this study are that 6 food stalls in the Tanjungwangi port area have met the minimum requirements for the Environmental Health Inspection, which is above a value of 80. The conclusion of this study is that the food stalls in Tanjungwangi port have a low risk of disease transmission due to poor food sanitation. result in a health emergency.